The male gaze explored: Ranking thinness and attractiveness of female body shapes. - Revital Naor-Ziv; Yaarit Amram-Veitz; Joseph Glicksohn (Journal for Person-Oriented Research)
The male gaze of the female body image in terms of thinness reveals its hierarchical structure: first torso, then legs, then arms. This is seen when in one task our male participants rank-ordered 8 composite images of a female body, derived from a Torso (thin vs. large) × Leg (thin/large vs. medium) × Arm (thin vs. large) design, from thinnest to largest. This primary focus on the torso is also critical in determining to what degree the female body image conforms to a desired hourglass shape. In a second task, the participants rank-ordered the same images from least attractive to most attractive. The rank-ordering of thinness was not readily predictive of the rank-ordering of attractiveness, and we found no clear end-structure underlying the female body image in terms of attractiveness. Nevertheless, in tracing the process of rating attractiveness, we can anchor the two ends of the series. The most attractive shapes were either Image 4 or Image 3, both instantiating a low waist-to-hip ratio (WHR). The first two choices for the least attractive shape were Image 1 (very thin) and Image 6 (very large). Great variability was found, however, in ranking the other body shapes, comprising composite images displaying an incompatibility of their various body parts. This results in a large number of paths for defining what attractiveness is for a particular male participant.